The Philippine-US Relations: Living or Leaving the Bandung Spirit? - Anna Rhodora Solar; John Matthew Poblete (Global South Review, 2015)
The Philippines had its own share of colonial past. Just as other Asian and African countries which were under the Western colonizers, the Philippines partook of the momentous event that proposed an alternative to the world order dominated by superpowers—the Bandung Conference. The principles collectively known as Bandung Spirit were embraced by the Philippines and had a clear understanding of its symbolic significance. Yet such understanding of these principles was coupled with compromises on the Philippines relations with the United States. Over the decades, the Philippines had to do a balancing act between its being sovereign, independent state and its recognition of the relevance of its past colonial master—the US. Hence, this raises the question of whether the Philippines is living or leaving the Bandung Spirit. Specifically, this paper assesses whether the Philippines still upholds the same Bandung Spirit in its traditional form or has it given a contemporary understanding of it. The paper argues that the Philippine-US relations remain to be an evident display of US presence in Southeast Asia albeit redefined to blend with the Bandung Spirit.